2021
DOI: 10.1016/j.saa.2020.119241
|View full text |Cite
|
Sign up to set email alerts
|

Experimental design approach for development of spectrofluorimetric method for determination of favipiravir; a potential therapeutic agent against COVID-19 virus: Application to spiked human plasma

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 93 publications
(75 citation statements)
references
References 13 publications
0
74
0
1
Order By: Relevance
“…The% degradation of the study was found to be 100.1%, which is allowed under ICH guidelines. Therefore, we hereby conclude that the developed method is accurate, accurate, sensitive, and reproducible for the quantitative estimation of Favipiravir bulk and its formulation [6,11,12,15,2,16].…”
Section: Degradation Studiesmentioning
confidence: 63%
See 4 more Smart Citations
“…The% degradation of the study was found to be 100.1%, which is allowed under ICH guidelines. Therefore, we hereby conclude that the developed method is accurate, accurate, sensitive, and reproducible for the quantitative estimation of Favipiravir bulk and its formulation [6,11,12,15,2,16].…”
Section: Degradation Studiesmentioning
confidence: 63%
“…5]. The label claim of the Favipiravir was 200 mg and we found it to be 204 mg in the tablet assay of Favipiravir using this developed method in Table 6 [6,2].…”
Section: Quantification Of Favipiravir In Formulationmentioning
confidence: 90%
See 3 more Smart Citations